2003
DOI: 10.1093/nar/gng129
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation by minisequencing and microarrays reveals accurate multiplexed SNP genotyping of whole genome amplified DNA

Abstract: Whole genome amplification (WGA) procedures such as primer extension preamplification (PEP) or multiple displacement amplification (MDA) have the potential to provide an unlimited source of DNA for large-scale genetic studies. We have performed a quantitative evaluation of PEP and MDA for genotyping single nucleotide polymorphisms (SNPs) using multiplex, four-color fluorescent minisequencing in a microarray format. Forty-five SNPs were genotyped and the WGA methods were evaluated with respect to genotyping suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 22 publications
1
95
2
1
Order By: Relevance
“…For eight loci assessed, amplification bias (over-and underrepresentation of sequences) was several orders of magnitude less than for the PCR-based WGA (Dean et al, 2002). Since then, MDA has been applied to many more eukaryotic studies, including the genomic sequencing and genotyping of humans and primates (Lovmar et al, 2003;Barker et al, 2004;Paez et al, 2004;Dickson et al, 2005;Jiang et al, 2005;Lu et al, 2005;Rö nn et al, 2006), insects (Gorrochotegui-Escalante and Black, 2003), fungi (Foster and Monahan, 2005;Gadkar and Rillig, 2005;Fernández-Ortuñ o et al, 2007) and additional applications in forensics and medicine (Hosono et al, 2003;Lasken and Egholm, 2003;Barber and Foran, 2006;Spits et al, 2006;Ballantyne et al, 2007).…”
Section: A Brief History Of Mdamentioning
confidence: 99%
“…For eight loci assessed, amplification bias (over-and underrepresentation of sequences) was several orders of magnitude less than for the PCR-based WGA (Dean et al, 2002). Since then, MDA has been applied to many more eukaryotic studies, including the genomic sequencing and genotyping of humans and primates (Lovmar et al, 2003;Barker et al, 2004;Paez et al, 2004;Dickson et al, 2005;Jiang et al, 2005;Lu et al, 2005;Rö nn et al, 2006), insects (Gorrochotegui-Escalante and Black, 2003), fungi (Foster and Monahan, 2005;Gadkar and Rillig, 2005;Fernández-Ortuñ o et al, 2007) and additional applications in forensics and medicine (Hosono et al, 2003;Lasken and Egholm, 2003;Barber and Foran, 2006;Spits et al, 2006;Ballantyne et al, 2007).…”
Section: A Brief History Of Mdamentioning
confidence: 99%
“…Cyclic minisequencing of the PCR products from both gDNA and cDNA, hybridization of the minisequencing reaction products to the captured oligonucleotides (cTags) on the slides and washing of the slides were performed as described previously. 41 Each sample (DNA and the corresponding cDNA) was run in triplicates on the same slide.…”
Section: Study Samplesmentioning
confidence: 99%
“…Our results have important implications for the conduct of whole genome studies. In studies where buccal samples have been extracted and stored properly, it will be possible to increase sample size and could obviate whole genome amplification before genotyping (11)(12)(13)(14)(15)(16)(17)(18)(19). Although the latter can generate large quantities of DNA from nanograms of highquality DNA, a number of studies have shown that the amplification step is not 100% accurate, and loss of heterozygosity, often clustered in GC-rich loci, can arise (12).…”
Section: Resultsmentioning
confidence: 99%